2016
DOI: 10.1089/aid.2015.0008
|View full text |Cite
|
Sign up to set email alerts
|

Tax and Semaphorin 4D Released from Lymphocytes Infected with Human Lymphotropic Virus Type 1 and Their Effect on Neurite Growth

Abstract: Human lymphotropic virus type 1 (HTLV-1) is a retrovirus causing HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), a neurodegenerative central nervous system (CNS) axonopathy. This virus mainly infects CD4 + T lymphocytes without evidence of neuronal infection. Viral Tax, secreted from infected lymphocytes infiltrated in the CNS, is proposed to alter intracellular pathways related to axonal cytoskeleton dynamics, producing neurological damage. Previous reports showed a higher proteolytic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…To test the effect of Tax and Sema4D (or the Tax/Sema4D complex) in neuronal cells, culture media from infected lymphocytes were added to PC12 cells during their differentiation to neuronal type, finding decreased neurite length as a result. The effect of HTLV-1-infected PBMC culture media was blocked by both anti-Sema4D and anti-Tax antibodies, suggesting neurite length reduction by a Tax/Sema4D complex [142]. In the same report, it was shown that infected lymphocytes strongly migrate in response to Sema4D using a trans-well system.…”
Section: Spastic Paraparesis Associated To Htlv-1mentioning
confidence: 84%
See 3 more Smart Citations
“…To test the effect of Tax and Sema4D (or the Tax/Sema4D complex) in neuronal cells, culture media from infected lymphocytes were added to PC12 cells during their differentiation to neuronal type, finding decreased neurite length as a result. The effect of HTLV-1-infected PBMC culture media was blocked by both anti-Sema4D and anti-Tax antibodies, suggesting neurite length reduction by a Tax/Sema4D complex [142]. In the same report, it was shown that infected lymphocytes strongly migrate in response to Sema4D using a trans-well system.…”
Section: Spastic Paraparesis Associated To Htlv-1mentioning
confidence: 84%
“…In the same report, it was shown that infected lymphocytes strongly migrate in response to Sema4D using a trans-well system. It was found that in the population of migrated lymphocytes, the levels of CRMP-2 phosphorylation at Ser522 were increased [142]. A change in Sema4Dmediated phosphorylation of CRMP-2 could be responsible for the increased motility.…”
Section: Spastic Paraparesis Associated To Htlv-1mentioning
confidence: 98%
See 2 more Smart Citations
“…Eluted fractions were analyzed by mass spectrometry to identify MAP6 partners. Interestingly, proteins in the CRMP family, members of which are known to play critical roles during semaphorin signaling ( Arbeille et al, 2015 ; Goshima et al, 1995 ; Niisato et al, 2012 ; Quintremil et al, 2016 ; Uchida et al, 2009 ; Yamashita et al, 2007 ), were identified as MAP6 partners. More precisely, we identified twelve specific peptides belonging to CRMP2, three specific peptides from CRMP4, two specific peptides from CRMP1, and six peptides shared by two or three of these CRMP proteins ( Supplementary file 1 ).…”
Section: Resultsmentioning
confidence: 99%